Mapping the evidence about what works to safely reduce the entry of children and young people into statutory care: a systematic scoping review protocol. Issue 8 (26th August 2019) - Brand, Sarah L; Morgan, Fiona; Stabler, Lorna; Weightman, Alison Lesley; Willis, Simone; Searchfield, Lydia; Nurmatov, Ulugbek; Kemp, Alison Mary; Turley, Ruth; Scourfield, Jonathan; Forrester, Donald; Evans, Rhiannon E
Abstract : Introduction: The increasing number of children and young people entering statutory care in the UK is a significant social, health and educational priority. Development of effective approaches to safely reduce this number remains a complex but critical issue. Despite a proliferation in interventions, evidence summaries are limited. The present protocol outlines a scoping review of research evidence to identify what works in safely reducing the number of children and young people (aged ≤18 years) entering statutory social care. The mapping of evidence gaps, clusters and uncertainties will inform the research programme of the newly funded Department for Education's What Works Centre for Children's Social Care. Methods and analysis: The review uses Arksey and O'Malley's scoping review methodology. Electronic database and website searches will identify studies targeting reduction of care entry, reduction of care re-entry and increase in post-care reunification. Supplementary searching techniques will include international expert consultation. Abstracts and full-text studies will be independently screened by two reviewers. Ten per cent of data abstraction will be independently conducted by two reviewers, with the remainder being extracted and then verified by a second reviewer. Descriptive numerical summaries and a thematic qualitative synthesis will be generated. Evidence will be synthesised according to primary outcome, intervention point (mapped across socioecological domains) and the realist EMMIE categorisation of evidence type (Effectiveness; Mechanisms of change; Moderators; Implementation; Economic evaluation). Ethics and dissemination: Outputs will be a conceptual evidence map, a descriptive table quantitatively summarising evidence and a qualitative narrative summary. Results will be disseminated through a peer-reviewed publication, conference presentations, the What Works Centre website, and knowledge translation events with policy-makers and practitioners. Findings will inform the primary research programme of the What Works Centre for Children's Social Care and the subsequent suite of systematic reviews to be conducted by the Centre in this substantive area.